EVALUATION OF THE COMPETITIVENESS OF CORN FOR GRAIN AND RAPESEED OF AGRICULTURAL ENTERPRISES OF UKRAINE (INNOVATIVE ECONOMY, 2021)
Hoisiuk L.V., Hoisiuk S.O. EVALUATION OF THE COMPETITIVENESS OF CORN FOR GRAIN AND RAPESEED OF AGRICULTURAL ENTERPRISES OF UKRAINEPurpose. The aim of the article is substantiation of the methodical approach to the calculation of the integrated index of product competitiveness and assessment of the level of competitiveness of corn for grain, winter rape seeds and colza of agricultural enterprises of Ukraine.Methodology of research. The following methods are used in the research process: analysis and synthesis - to study the indicators of cultivation and sale of corn for grain, winter rape and colza in agricultural enterprises of Ukraine; abstract and logical - for formulation of conclusions and generalizations; cartographic - to analyse the competitiveness index of maize for grain, winter rape and colza.Findings. A set of indicators for calculating the integrated index of competitiveness of the studied crops: yield, sales price of 1 quintal of production, total cost of production, sales, market share, profit per 1 quintal of sales, profit per 1 ha of sown area, marketability level, level profitability of production. The competitiveness of corn for grain, winter rape and colza grown by agricultural enterprises in the context of the regions of Ukraine was assessed. A scale for assessing the competitiveness of corn for grain, winter rape and colza was developed.Originality. A method for assessing the level of competitiveness of corn for grain, winter rape and colza, on the basis of which it is possible to form effective ways to increase it, is proposed.Practical value. The proposed methodological approach to assessing the competitiveness of corn for grain, winter rape and colza of agricultural enterprises allows to analyse and substantiate the results from large data sets, take into account the impact of stimulants and destimulators of selected traits on the final result, combine and use criteria and indicators .Key words: corn for grain, rapeseed, colza, assessment of product competitiveness, integrated competitiveness index, agricultural enterprises.
Keywords: Key words; corn for grain; rapeseed; colza; assessment of product competitiveness; integrated competitiveness index; agricultural enterprises.